Microsphere Assisted Super-resolution Optical Imaging of Plasmonic Interaction between Gold Nanoparticles. Issue 1 (December 2017) - Hou, Beibei; Xie, Mengran; He, Ruoyu; Ji, Minbiao; Trummer, Sonja; Fink, Rainer; Zhang, Luning
Abstract Conventional far-field microscopy cannot directly resolve the sub-diffraction spatial distribution of localized surface plasmons in metal nanostructures. Using BaTiO3 microspheres as far-field superlenses by collecting the near-field signal, we can map the origin of enhanced two-photon photoluminescence signal from the gap region of gold nanosphere dimers and gold nanorod dimers beyond the diffraction limit, on a conventional far-field microscope. As the angle θ between dimer's structural axis and laser polarisation changes, photoluminescence intensity varies with a cos4 θ function, which agrees quantitatively with numerical simulations. An optical resolution of about λ/7 (λ: two-photon luminescence central wavelength) is demonstrated at dimer's gap region.